Acute and chronic histopathologic changes in wild type or TLR-2-/-, TLR-4-/-, TLR-6-/-, TLR-9-/-, CD14-/-, and MyD-88-/- mice experimentally infected with Plasmodium chabaudi - Silva, Ana Patrícia C.; Rodrigues, Soraia C. O.; Merlo, Fernanda A.; Paixão, Tatiane A.; Santos, Renato L. (Brazilian Journal of Veterinary Pathology, 2011)
Malaria is caused by protozoan parasites of the genus Plasmodium, which is transmitted by Anopheline mosquitoes. Experimental murine models using rodent malaria are useful for studying pathologic aspects of severe malaria. We evaluated histopathologic lesions of TLR-2-/-, TLR-4-/-, TLR-6-/-, TLR-9-/-, CD14-/- and MyD88-/- mice experimentally infected with Plasmodium chabaudi. Frequencies and severity of microscopic lesions in the spleen and liver at one and four weeks post infection (wpi) were determined. At one wpi, adherence of macrophages to the endothelial surface was the most evident change, whereas at four wpi there was marked accumulation of cytoplasmic pigment in macrophages in the liver and spleen. Lesions were not markedly influenced by the absence of TLRs, MyD88 or CD14. Our findings suggest that acute and chronic phases of murine infection with P. chabaudi are characterized by distinct lesions. In addition, TLRs and MyD88 are not essential to promote these lesions during P. chabaudi infection.